Seminar Parenting: Mendidik Anak Dengan Keteladanan dan Cinta - Rully Angraeni Safitri; Siti Abadiyah; Basirun Basirun; Siti Hafidzoh; Khaerunnisa Yulia Handayani (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
The seminar "Educating Children with Exemplary Behavior and Love," held on August 11, 2024, at the Community Center RW 05, Kelurahan Sangiang Jaya, aimed to equip parents with knowledge about the importance of role modeling and affection in child education. The methods used included a presentation by a speaker and a question-and-answer session. The results of the seminar showed that consistent application of role modeling and affection can improve the parent-child relationship and enhance parenting effectiveness. The implications of these results highlight the need for parents to integrate these principles into their daily lives to support optimal child development. Participants explored the importance of being a good example in daily life and how role modeling can shape children’s character and behavior. Additionally, the seminar discussed how to create a loving environment that provides emotional support for children's psychological and social development. The seminar aimed to help parents build healthy and harmonious relationships with their children and prepare them to become empathetic and responsible individuals.